Gynecologic cancers in pregnancy: guidelines of a second international consensus meeting - Amant, Frédéric; Halaska, Michael J; Fumagalli, Monica; Dahl Steffensen, Karina; Lok, Christianne; Van Calsteren, Kristel; Han, Sileny N; Mir, Olivier; Fruscio, Robert; Uzan, Cathérine; Maxwell, Cynthia; Dekrem, Jana; et al. (International journal of gynecological cancer, 2014)
OBJECTIVES: This study aimed to provide timely and effective guidance for pregnant women and health care providers to optimize maternal treatment and fetal protection and to promote effective management of the mother, fetus, and neonate when administering potentially teratogenic medications. New insights and more experience were gained since the first consensus meeting 5 years ago. METHODS: Members of the European Society of Gynecological Oncology task force "Cancer in Pregnancy" in concert with other international experts reviewed the existing literature on their respective areas of expertise. The summaries were subsequently merged into a complete article that served as a basis for discussion during the consensus meeting. All participants approved the final article. RESULTS: In the experts' view, cancer can be successfully treated during pregnancy in collaboration with a multidisciplinary team, optimizing maternal treatment while considering fetal safety. To maximize the maternal outcome, cancer treatment should follow a standard treatment protocol as for nonpregnant patients. Iatrogenic prematurity should be avoided. Individualization of treatment and effective psychologic support is imperative to provide throughout the pregnancy period. Diagnostic procedures, including staging examinations and imaging, such as magnetic resonance imaging and sonography, are preferable. Pelvic surgery, either open or laparoscopic, as part of a treatment protocol, may reveal beneficial outcomes and is preferably performed by experts. Most standard regimens of chemotherapy can be administered from 14 weeks gestational age onward. Apart from cervical and vulvar cancer, as well as important vulvar scarring, the mode of delivery is determined by the obstetrician. Term delivery is aimed for. Breast-feeding should be considered based on individual drug safety and neonatologist-breast-feeding expert's consult. CONCLUSIONS: Despite limited evidence-based information, cancer treatment during pregnancy can succeed. State-of-the-art treatment should be provided for this vulnerable population to preserve maternal and fetal prognosis. SUPPLEMENTARY INFORMATION: Supplementary data on teratogenic effects, ionizing examinations, sentinel lymph node biopsy, tumor markers during pregnancy, as well as additional references and tables are available at the extended online version of this consensus article, go to http://links.lww.com/IGC/A197.
Keywords: nádorové komplikace v těhotenství; protinádorové látky; nádory ženských pohlavních orgánů; Female; Pregnancy Complications, Neoplastic; Antineoplastic Agents; Genital Neoplasms, Female; Neonatology; Pregnancy; Humans; ženské pohlaví; lidé; vedení porodu; Delivery, Obstetric; těhotenství; neonatologie